Identifikasi Kandungan Deposit Lensa Kontak Pasca Pemakaian - Lilis Hadiyati; Arief Witjaksono; Putri Gita Aprilia (Sehat MasadaJurnal, 2020)
Contact lenses are visual aids that provide comfort for activities and are aesthetically better, but inappropriate use or care of it can cause mild to severe complications. Poor hygiene and compliance in the use and care of contact lenses can be a risk factor for inflammation in the eye, this is because within a few minutes contact lenses become quickly coated with various tear film components in the form of proteins, lipids, and mucus. This component is called a deposit. The purpose of this study was to identify the deposit content found in post-use contact lenses. This research is a descriptive study with cross sectional approach, in which a sample of 5 people were asked to use contact lenses within 8 hours every day for 2 consecutive weeks. The results showed a deposit on contact lenses in the form is protein, lipid, calcium, and makeup contamination in each sample. This is likely due to exposure to dust, the environment and poor hygine of contact lens users, including in terms of how to care. Thus we need simpler educational methods and contact lens care procedures to improve the compliance of contact lens users in maintaining care.